Some aspects of treating inflammatory intestinal diseases - E. Yu. Plotnikova; E. Yu. Chashkova (Лечащий Врач)
From modern perspectives, the article considers issues of etiopathogenesis, diagnostics and treatment of inflammatory intestinal diseases – ulcerative colitis and Crohn’s disease. Modern principles of treatment for patients with inflammatory intestinal diseases were given. A clinical case with non-typical complicated course of Crohn’s disease was described.